2014
DOI: 10.1123/jtpe.2013-0153
|View full text |Cite
|
Sign up to set email alerts
|

High School Students’ Attitudes Toward Fitness Testing

Abstract: The purpose of this study was to investigate the attitudes of high school students toward fitness testing. An instrument containing 18 items and four factors measuring student's attitudes toward fitness testing: cognitive, affect-enjoyment, affect-feelings, and affect-teacher was completed by 524 boys and 675 girls (N = 1199). MANOVA indicated significant differences among the dependent variables for grade and gender. A stepwise discriminant function analysis (DFA) indicated affect-feelings then affect-enjoyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 42 publications
(81 reference statements)
5
35
0
3
Order By: Relevance
“…The low-to-moderate levels of interest reported in this study are consistent with two previous studies (Hopple & Graham, 1995;Mercier, 2011), yet inconsistent with Sampson's (2008) result. In Sampson's study (2008), about 86% of the students reported very positive perceptions of fitness testing, whereas this current study displayed inadequate interest among the students (mean values at around or below 3 on a five-point scale).…”
Section: Gender Differences In Interestsupporting
confidence: 86%
See 2 more Smart Citations
“…The low-to-moderate levels of interest reported in this study are consistent with two previous studies (Hopple & Graham, 1995;Mercier, 2011), yet inconsistent with Sampson's (2008) result. In Sampson's study (2008), about 86% of the students reported very positive perceptions of fitness testing, whereas this current study displayed inadequate interest among the students (mean values at around or below 3 on a five-point scale).…”
Section: Gender Differences In Interestsupporting
confidence: 86%
“…Some students, particularly those who performed poorly, would even make excuses to "dodge" the test (Hopple & Graham, 1995). Mercier (2011) reported that secondary school students mostly had a neutral-to-positive attitude toward fitness testing, although boys had a higher overall positive attitude than girls. These aerobic fitness tests are often criterion-referenced, and meeting the set of criteria appears to be demanding for many children and adolescents.…”
Section: Student Perception and Performances In Fitness Testingmentioning
confidence: 98%
See 1 more Smart Citation
“…Researchers over the past six decades have identified a number of problematic issues regarding the use of HRF testing in school settings. These were found to be the following: Fitness testing and fitness education are not connected (Keating and Silverman, 2009; Silverman et al, 2008; Zhu et al, 2018), resulting in limited, if any, use of fitness test results in PE programmes (SHAPE America, 2012); Publicly administered fitness testing could result in non-confidential scores among students (Keating, 2003; Martin et al, 2010; Silverman et al, 2008), which might further negatively impact students’ attitudes toward fitness testing (Mercier and Silverman, 2014; Zhu et al, 2011) and is particularly detrimental to students who perform poorly on the test (Zhu et al, 2018); Fitness testing is taken in PE classes with a large number of students being tested simultaneously and it is difficult for a PE teacher to complete the test battery in a timely manner (Corbin, 2004; Liguori and Mozumdar, 2009; Silverman et al, 2008); Students found fitness testing competitive or boring due to constant use of the same test items (e.g. one-mile run/PACER, push-ups, curl-ups, and sit-ups) over decades (Keating, 2003; Silverman et al, 2008); Both students and teachers are not held accountable for fitness testing results leading to minimal effort (Zhu et al, 2018), producing limited, if any, motivational effects; Students must take the tests on a specific day or week when students may be physically sick or the weather is too cold or hot for outdoor testing (Martin et al, 2010); and The validity and reliability of some testing items such as sit-ups and push-ups are questionable (Bianco et al, 2015; Rowland, 1995), as many students cannot perform them correctly (Zhu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have examined individual tests, limited research has been performed on whole test batteries or on school-based physical fitness testing practices (Cale & Harris, 2009). The most researched area on school-based physical fitness testing includes studies on attitudes toward physical fitness testing, which generally found students' attitudes toward fitness testing to be negative or neutral, whereas teachers' attitudes were only slightly positive (Ferguson et al, 2007;Hopple & Graham, 1995;Mercier & Silverman, 2014). However, research examining current physical fitness testing practices in the schools is limited (Keating, 2003).…”
mentioning
confidence: 99%